India's Role in the Context of the International Political and Security System as a Regional Hegemony in South Asia - Anjan Ananda Sen (International Journal of Science and Society, 2020)
This paper discusses the author's argument regarding India's strategy to become a regional hegemony in the South Asian region. As a country with fairly high economic growth, and superior defense and political stability capabilities compared to other countries in South Asia, the authors describe the capabilities of India as a dominant actor in the region by using the Regional Hegemony theory proposed by John Mearsheimer, and the concept of Foreign Policy The land of Robert Keohan